Long-Term Habitat Degradation Drives Neotropical Macrophyte Species Loss While Assisting the Spread of Invasive Plant Species - Salgado, Jorge; Vélez, María I.; Caceres-Torres, Laura C.; Villegas-Ibagon, Jose A.; Bernal-Gonzalez, Laura C.; Lopera-Congote, Laura; Martinez-Medina, N. Melissa; González-Arango, Catalina (Frontiers in Ecology and Evolution, 2019)
The spread of invasive macrophyte species is a pressing threat to neotropical shallow lakes. Yet there are few studies addressing the full extent of biotic and abiotic changes that may occur in response to invasive species. Less is known of how other human-induced stressors such as eutrophication and lake draining may interact over time with invasive macrophytes to influence biodiversity. We combined limnological observations with paleoecological data from Fúquene Lake, Colombia, a eutrophic neotropical shallow lake, to provide information on the current and long-term (decades-centuries) dynamics of the spread of two well-established invasive plants Eichhornia crassipes and Egeria densa. We found a unique in macrophyte species composition in areas currently dominated by Egeria and Eichhornia. Eichhornia-dominated areas had 14 macrophyte species, turbid (secchi=19 ± 6 cm) and poorly oxygenated (3.94 ± 2.61 ppm) waters whereas Egeria-rich areas supported 5 species and had clearer (secchi=51 ± 12 cm) and better-oxygenated (6.06 ± 2.4 ppm) waters. Historical macrophyte community shifts were linked to eutrophication and lake level variation and characterized by the loss of charophytes and bryophytes before 1500 CE and subsequent reductions in Nymphaea sp., Potamogeton illinoensis and Najas guadalupensis in the early 1900s (lake draining). Eichhornia crassipes (since 1500 CE) and E. densa (early 1900s) occurred well before proposed dates of introduction (1950s and 1990 respectively). Both species have rapidly expanded since the 1990s along with Azolla filiculoides in response to an inflow water diversion scheme and heavy nutrient loads. Our results suggest that the spread of Eichhornia and Egeria was not responsible for native macrophyte species loss, but that their current dominance is exerting synergistic and antagonistic secondary effects on plant assemblages through habitat modification, competitive exclusion and promotion of habitat heterogeneity across the lake. It could therefore be misleading to suggest that invasive plants causes macrophyte species loss in degraded lakes. We suggest that aggressive species like Eichhornia, Azolla, and Egeria require hydrologically stable and eutrophic environments to spread; thus, management actions should focus on controlling these two factors. Our study demonstrates the need to use a long-term approach to fully-understand the effects of invasive macrophytes.